Synthesis of Some New Photosensitizer Cyanine Dyes - Sharma, K.P.; Dikshit, S.N.; K. Sharma, Harendra (Asian Journal of Chemistry, 2010)
A series of new cyanine dyes has been synthesized by the reaction of p-dimethylamino cinnamaldehyde with meth and ethiodide of 5-arylamino-2-methyl-1,3,4-thiadiazole and quinaldines in ethanol using piperidine as catalyst. Absorption spectra structure relationships of the synthesized cyanine dyes were discussed.